PROVISION 12/2020 OF CGJ / SP AS AN INSTRUMENT FOR CONCRETEING CITIZENSHIP DURING PANDEMIC COVID 19 (Anais do Congresso Brasileiro de Processo Coletivo e Cidadania, 2020)
The purpose of this article is to demonstrate that the Provision 12/2020 issued by “Corregedoria Geral de Justiça” from São Paulo state’s has become an effective means of concretizing citizenship by enabling the practice of notarial acts electronically during the pandemic generated by Covid 19. Therefore, through the analysis of the essentiality of the notary function for the realization of various legal business and considering that social distance is necessary at this moment to prevent the spread of the disease, it is evident that the Provision allowed the economy not to was stagnant and that through it the civil element of the concept of citizenship envisaged by Marshal was not violated, allowing the right to property and to make contracts not to be interrupted during the crisis.